Quantitative metrics for generative justice: graphing the value of diversity - Callahan, Brian Robert; Hathaway, Charles; Krishnamoorthy, Mukkai (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
Scholarship utilizing the Generative Justice framework has focused primarily on qualitative data collection and analysis for its insights. This paper introduces a quantitative data measurement, contributory diversity, which can be used to enhance the analysis of ethical dimensions of value production under the Generative Justice lens. It is well known that the identity of contributors—gender, ethnicity, and other categories—is a key issue for social justice in general. Using the example of Open Source Software communities, we note that that typical diversity measures, focusing exclusively on workforce demographics, can fail to fully illuminate issues in value generation. Using Shannon’s entropy measure, we offer an alternative metric which combines the traditional assessment of demographics with a measure of value generation. This mapping allows for previously unacknowledged contributions to be recognized, and can avoid some of the ways in which exclusionary practices are obscured. We offer contributory diversity not as the single optimal metric, but rather as a call for others to begin investigating the possibilities for quantitative measurements of the communities and value flows that are studied using the Generative Justice framework.